Antecedents and Consequences of Destination Brand Attachment: Empirical Study on Surya Waterboom - Rahmayanti, Nynda (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
—Surya Waterboom as a tourist destination faces competition among its competitors. To distinguish one tourist destination from another, Surya Waterboom needs a brand as the identity of a tourist destination. This study aims to determine the antecedents and consequences of destination brand attachment to the Surya Waterboom tourist destination. The sample in this study was conducted using the Slovin formula as many as 100 respondents. The sampling technique used was purposive sampling. Data were obtained using a questionnaire measured by a Likert scale. This study uses Partial Least Square regression analysis using SmartPLS 3.0 software to process the data. The results showed that memorable tourist experiences had a significant effect on destination brand attachments, memorable tourist experiences did not have a significant effect on the intention to visit destinations, perceived quality had a significant effect on destination brand attachments, and destination brand attachments had a significant effect on the intention to revisit a destination